Salt intake- related knowledge, attitudes, and practices among Jordanian adults - Majeed, Zeina A.; Barham, Rawhieh; Al-Jawaldeh, Ayoub; Ahmad, Nada; Khader, Yousef (Narra Sains Indonesia, 2025)
High salt consumption is a worldwide public health problem, and its magnitude varies considerably among different communities. This study aimed to assess Jordanian adults’ knowledge, attitudes, and practices related to salt intake and to examine how these domains differed between genders. A quantitative cross-sectional survey was conducted using a multi-stage sampling technique to select a representative sample from the population of Amman, Jordan. Data were collected through a structured, validated questionnaire administered by trained interviewers between November and December 2021. The findings indicate that the majority of participants (70.8%) did not know the maximum recommended daily salt intake and reported not reading food labels when purchasing food. Almost half of the participants (48.2%) reported always adding salt while cooking, and 14.6% reported always adding table salt after cooking. The most commonly reported practices to reduce salt intake included using spices other than salt while cooking (67.2%) and avoiding or reducing the consumption of salt-rich foods. Significant gender differences were observed in knowledge, attitudes, and practices (KAP) toward salt intake. Females demonstrated greater awareness of recommended salt intake and associated health risks, and were more likely to engage in practices aimed at reducing salt consumption, such as avoiding high-salt foods and using alternatives in cooking. In contrast, males were more likely to report misconceptions, limited use of food labels, and higher engagement in unhealthy practices such as daily smoking and lower awareness of low-salt alternatives. In conclusion, this study showed that Jordanian adults have relatively limited knowledge about salt intake, and their practices regarding salt consumption are inappropriate. Therefore, there is a need to adopt long-term strategies to reduce salt intake among the Jordanian population and mitigate its negative impacts on community health.